Analisis Perencanaan dan Pengendalian Obat Poli Kandungan dengan Metode ABC Indeks Kritis di Instalasi Farmasi Rawat Jalan Rumah Sakit Dr. Hafiz Cianjur: Analysis of Drug Planning and Control in the Obstetrics Outpatient Clinic Using the ABC Critical Index Method tt the Outpatient Pharmacy Department of Dr. Hafiz Hospital, Cianjur - Derry Syamsuardi; Riasa Barata Nian; Julia Totong (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2024)
Pharmaceutical services are very important within the scope of hospitals. Good procurement planning can support pharmaceutical services to run better. The large number of cases in the field regarding empty medicines or requests for medicines that do not comply with the hospital formulary makes it necessary to carry out an analysis using the ABC Critical Index method. This research aims to determine the accuracy of planning and procurement of the Gynecology Poly in the RS Dr. Hafiz Outpatient Pharmacy Installation. This research uses a non-experimental, retrospective case study design, focusing on drug planning and control based on the ABC Critical Index analysis method. The research findings showed that of the 64 types of poly-gynecological drugs, 14 drug units (21.88%) were group A, while for group B, there were 17 drug units (26.56%), and for group C, there were 33 drug units (51, 56%). It is recommended that drugs in groups A and B continue to be provided in the next procurement, and the need for group C needs to be reviewed for the next period.